2021
DOI: 10.3389/fchem.2021.739802
|View full text |Cite
|
Sign up to set email alerts
|

Shielding Unit Engineering of NIR-II Molecular Fluorophores for Improved Fluorescence Performance and Renal Excretion Ability

Abstract: Molecular fluorophores emitting in the second near-infrared (NIR-II) window with good renal excretion ability are favorable for in vivo bio-imaging and clinical applications. So far, renally excretable fluorophores are still less studied. Understanding the influences of molecular structure on optical properties and renal excretion abilities are vital for fluorophore optimization. Herein, a series of shielding unit-donor-acceptor-donor-shielding unit (S-D-A-D-S) NIR-II molecular fluorophores are designed and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Polyethylene glycol-2000 (PEG 2000 )-alkyne (terminal functionalized) was used to impart these two molecules with solubility in aqueous media via using a click-reaction scheme (Scheme S3†). 26,47 According to gel exclusion chromatography (SEC) data, the average molecular weight ( M w ) of PEGylated product was 5500, indicating that PEGylation did not occur quantitatively. The incomplete occurrence of this click reaction may be due to the steric hindrance between the backbone structure and the PEG chain.…”
Section: Resultsmentioning
confidence: 99%
“…Polyethylene glycol-2000 (PEG 2000 )-alkyne (terminal functionalized) was used to impart these two molecules with solubility in aqueous media via using a click-reaction scheme (Scheme S3†). 26,47 According to gel exclusion chromatography (SEC) data, the average molecular weight ( M w ) of PEGylated product was 5500, indicating that PEGylation did not occur quantitatively. The incomplete occurrence of this click reaction may be due to the steric hindrance between the backbone structure and the PEG chain.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a shielding unit (S, such as alkyl chain-substituted fluorene) could be introduced to weaken intermolecular interactions among conjugated backbones, resulting in improved fluorescence quantum yields (QYs) for S-D-A-D-S fluorophores [ 19 , 20 ]. It has also been demonstrated that rational engineering of the D unit can induce substantial tuning on the optical properties and pharmacokinetics of these fluorophores [ 14 , 21 25 ]. The steric size and hydrophobicity of D unit can effectively alter the backbone geometry and intermolecular interaction, which are closely correlated with the absorption or emission wavelength, QY, and absorption coefficient ( ε ) of fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…Organic fluorophores are favourable for biological applications due to their improved biocompatibility and structural tunability. To date, numerous organic molecular fluorophores, including polymethine fluorophores, [12][13][14] donor-acceptor-donor (D-A-D) fluorophores, [15][16][17][18][19][20][21][22][23] and A-D-A fused-ring acceptor fluorophores, [24][25][26][27] have been developed for NIR-II bioimaging. Among them, D-A-D fluorophores are an interesting type as their fluorescence emission wavelengths can be effectively tuned by varying D/A units.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] It has been demonstrated that molecular engineering of the donor unit plays a key role in improving QYs for D-A-D type NIR-II fluorophores, especially in aqueous conditions. [16][17][18][19] Thiophene-and benzene-based donor units are generally used to construct NIR-II fluorophores, and thiophene is more favourable than benzene as it could afford larger conjugation for longer emission wavelengths. Unfortunately, NIR-II fluorophores with pristine thiophene donors exhibit poor QYs in aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%